A Comparative Analysis of Functional Outcomes between Lateral and Posterolateral Approaches in Total Hip Arthroplasty - Farzad Amouzadeh Omrani; Sina Afzal; Mojtaba Baroutkoub; Sohrab Salimi; Hasan Barati; Sina Azadnajafabad; Saeed Kokly; Mohammad Mehdi Omidian (Advanced Biomedical Research)
Background: Total hip arthroplasty (THA) stands as the definitive gold standard treatment for degenerative hip disorders. Various approaches have been proposed for THA, each with its own set of advantages and disadvantages. This study aimed to compare the initial functional outcomes of the lateral and posterolateral approaches to determine the approach with superior functional outcomes. Materials and Methods: Through a retrospective cohort study, THA candidates over a 1-year period were analyzed. Patients who underwent surgery via the lateral or posterolateral approaches were included. Demographic characteristics of patients and postoperative outcomes were compared. Patients were followed up for 1 and 6 months to evaluate their functional outcomes using the Harris Hip Score (HHS). Results: A total of 50 THA candidates, divided into two groups of lateral (N = 25) and posterolateral (N = 25) approaches, were evaluated in this study. Comparison of demographic data revealed a significant difference in height and body mass index between the two groups (P < 0.05), whereas age and weight showed no significant difference (P > 0.05). The mean HHS and range of motion significantly improved in each group after 6 months (P < 0.001). No significant difference was observed between the lateral and posterolateral approaches in terms of HHS and hip range of motion (P > 0.05). Conclusion: The results of this study demonstrate no significant difference between the outcomes of the lateral and posterolateral approaches for THA. The choice of the optimal THA approach remains contingent on the surgeon’s experience and the patient’s preference.